Penyelesaian Masalah Economic Dispatch Menggunakan Equilibrium Optimizer - Zebua, Osea; Ginarsa, I Made; Ari Nrartha, I Made (Jurnal Teknik Elektro, 2021)
This paper presents a metaheuristic method, namely Equilibrium Optimizer (EO) to solve the economic dispatch (ED) problem. The main objective function to be achieved is to minimize the total fuel costs of all generating units to meet the total load demand and to satisfy various operating constraints. Three case studies are used to test the effectiveness of the EO method in solving ED problems, they are three generators case, six generators case, and fifteen generators case. The simulation of solving ED problems using the EO method is implemented using MATLAB software and is carried out 30 times for each case study. The results of EO method are compared with Particle Swarm Optimization (PSO), Grey Wolf Optimizer (GWO), and Whale Optimization Algorithm (WOA) methods. The simulation results show that the EO method can solve the ED problem more optimal than all other comparison methods for all the case studies by producing the minimum total fuel costs.